TELAAH HISTORIS DALAM KEBIJAKAN HARGA MENURUT PERSPEKTIF ISLAM - Ilham, Muhammad; Saifullah, Saifullah (STAI Darul Qalam Tangerang, 2023)
This study aims to examine the concept of price policy in an Islamic perspective. In Islamic business, profitability must be balanced with the need to provide efficiency, reliability and courteous service and good quality at a reasonable price for consumers. This research is library research, which means this research leads to the results of a literature review and without going through research specifically in the field. The results show that Islamic Business emphasizes mutual satisfaction and approval or pleasure (taradin) between buyers and sellers as well as the need to be honest in all business transactions to get blessings from Allah. Limitation of profit maximization can be an alternative and acceptable as long as it fulfills the principles that are very in line with the Islamic concept of social justice and being responsible for the welfare of others